Navigating Indonesia’s Engagement with China’s Belt and Road Initiative: Strategic Leverage Analysis - Rahmahwati, Isti Nur; Riyanto, Budi (Journal of Integrative International Relations, 2025)
This study analyzes Indonesia’s engagement with China’s Belt and Road Initiative (BRI) in the context of strategic leverage, utilizing Maritime Axis narrative as its instrument. Instead of relying on Colley’s and Noort’s buy-in framework, this article develops the interplay of narrative and diplomatic engagement within the framework of strategic leverage. Strategic leverage is an alternative framework unveiling how Indonesia with its middle-level of power proactively and flexibly shape and navigate its engagement with China’s BRI, moving beyond a binary framework of acceptance and rejection of the BRI. The leverage as a bottom-up process is used to pursue strategic goals, balancing the interaction of materialism and ideational dimension. Focusing on Indonesia, this study highlights three forms of leverage: bargaining, investment, and resource leverage. Qualitative methodology is applied in this study, concerning narrative and behavioral analysis. The result is that Indonesia’s engagement with China’s BRI is part of the country’s strategic leveraging cycle rather solely a buy-in behavior as proposed by Colley and Noort.